Case report: Concurrent MOG antibody-associated disease and latent infections in two patients - Kulsvehagen, Laila; Woelfle, Tim; Ayroza Galvão Ribeiro Gomes, Ana Beatriz; Lipps, Patrick; Neziraj, Tradite; Flammer, Julia; Leuzinger, Karoline; Derfuss, Tobias; Kuhle, Jens; Papadopoulou, Athina; Pröbstel, Anne-Katrin (Frontiers in Immunology, 2024)
Objectives: Myelin oligodendrocyte glycoprotein (MOG) antibody-associated disease (MOGAD) is frequently preceded by infections. The underlying pathomechanism, however, remains poorly understood. Here, we present clinical data of two MOGAD patients with concurrent syphilis infection and investigate the reactivity of patient-derived antibodies to MOG and Treponema pallidum (T. pallidum).Methods: Longitudinal serum samples and soluble immunoglobulins in single B cell supernatants were measured for MOG-reactivity by a live cell-based assay. Reactivity against T. pallidum was assessed by enzyme-linked immunosorbent assay.The two patients presented MOGAD and concurrent latent syphilis infection, manifesting as cervical myelitis and unilateral optic neuritis, respectively. The first patient had been living with HIV on antiretroviral therapy, the second was concomitantly diagnosed with chronic hepatitis B infection. Upon screening of B cell supernatants, we identified reactivity to MOG or T. pallidum. Notably, one B cell showed reactivity to both antigens.The co-existence of MOGAD diagnoses and latent syphilis, alongside the identification of antibody reactivity to MOG and T. pallidum underscore the potential pathomechanistic link between syphilis infection and subsequent autoimmune neuroinflammation. Cross-reactivity between MOG and T. pallidum antibodies remains to be validated on a molecular level, and further characterization of infectious triggers associated with MOGAD is needed.